Upstreamness, social upgrading and gender: Equal benefits for all? - Nicola Gagliardi; Benoît Mahy; François Rycx (National Bank of Belgium, 2018)
This paper examines social upgrading related to firms' participation in Global Value Chains (GVCs) from a developed countries' perspective. Merging detailed matched employer-employee data relative to the Belgian manufacturing industry with unique information on firm-level upstreamness, we investigate whether workers on the upstream stage of GVCs benefit from higher wages. We also enrich our analysis with a gender dimension. Unconditional quantile regressions and decomposition methods reveal that firms' upstreamness fosters workers' social upgrading. Nevertheless, gains are found to be unequally shared among workers. Male top-earners are the main beneficiaries; whereas women, irrespective of their earnings, appear to be unfairly rewarded.
Keywords: F61; F66; J16; J31; 330; Social upgrading; Global value chains; Wages; Gender; Developed countries